Technological Foundations for Drilling Rapal Deposits Under Difficult Conditions (Texas Journal of Engineering and Technology, 2022)
The article discusses the difficulties of drilling salt deposits, their prevention and elimination, the chemicals used, the requirements for the drilling fluid, its preparation, water permeability, density, viscosity, static shear parameters and lubricants, as well as the definition of filtration parameters